A rollout heuristic algorithm for order sequencing in robotic compact storage and retrieval systems. (1st October 2022) - Ko, Dayoung; Han, Jinil
Abstract: Robotic compact storage and retrieval systems (RCSRSs) are robotized automated warehousing systems that are being increasingly used in several companies around the world owing to their efficient usage of space and low cost. In RCSRSs, a vertical stacking approach is used. Thus, to retrieve a target bin, all bins located above it must be reshuffled, causing the depth-wise position of bins to change repeatedly. Therefore, the amount of work required for a robot to process bins depends heavily on the sequence in which orders are processed. In this study, we address the problem of determining the processing sequence for a given set of orders in the RCSRS. According to the complexity of this problem, we propose a rollout heuristic algorithm to find a high-quality solution within a short computation time. We also introduce several strategies to improve the performance of the proposed algorithm. Through computational experiments on random instances generated based on real-world data, we demonstrate that the proposed rollout heuristic algorithm can be effectively applied to real-world instances. Highlights: A new sequencing problem arising in the robotized automated warehouse is discussed. A rollout heuristic algorithm is proposed to obtain high-quality solutions. Various performance improvement strategies are introduced. The effectiveness and efficiency of the proposed heuristic are verified.